(untitled) (Research, Society and Development, 2021)
The teacher performs, in most cases, a solitary work, in the midst of inadequate conditions for the development of their work, creating situations favorable to stress in which their biopsychosocial aspect is compromised. In order to identify the incidence of the level of stress at work in university professors, a descriptive cross-sectional observational study was carried out. Work stress was measured using the adapted version by Theorell of the JCQ questionnaire (demand-control model) by Karasek, containing questions to assess the Psychological and Control Demand Dimension, consisting of 11 items, and the Social Support Dimension with 6 items. In the results found from the 102 teachers surveyed, 72.9% are female, 40% are under the age of 34, 57.1% said they did not have children and 58.6% declared themselves white. In view of what was found in the JCQ questionnaire, 48.6% of the teachers are in the Low-strain quadrant (low demand and high control). In several studies it was found as results that teachers have a high level of stress at work, especially female individuals, and women, when compared to men, had higher averages of development of work-related illnesses. It was evident that the majority of teachers are female who become a public directly exposed to stress, showing that this population deserves a little more attention.